(untitled) (Contemporary Journal of Social Science Review, 2024)
The purpose of the present study was to explore Personal Values (Self- transcendence, Self-enhancement, Openness to change, Conservation) as correlates of Love attitude (Eros, Ludus, Storge, Pragma, Mania, Agape) in young adults. A total of 600 Pakistani adults aged 18 to 50 participated in the study who were involved in a romantic relationship. The Portrait Value Questionnaire (PVQ-57RR) and Love Attitude Scale (LAS) were used in the study. The findings demonstrate a negative relationship between self-transcendence (personal value) and ludus and mania (love attitudes), and a negative relationship between self-enhancement and love attitudes (eros, mania, and agape). Similarly, openness was found to be negatively correlated with storge, mania, and agape (love styles) and conservation was also found to be negatively correlated with ludus, pragma, and mania (love attitudes). The pattern of these results suggests that individuals’ personal values impact their love attitudes towards their romantic relationships.